Non‐Typical Supershear Rupture: Fault Heterogeneity and Segmentation Govern Unilateral Supershear and Cascading Multi‐Fault Rupture in the 2021 Mw ${M}_{w}$7.4 Maduo Earthquake - J. N. Hayek; M. Marchandon; D. Li; L. Pousse‐Beltran; J. Hollingsworth; T. Li; A.‐A. Gabriel (Geophysical Research Letters)
Abstract Previous geodetic and teleseismic observations of the 2021 Mw7.4 Maduo earthquake imply surprising but difficult‐to‐constrain complexity, including rupture across multiple fault segments and supershear rupture. Here, we present an integrated analysis of multi‐fault 3D dynamic rupture models, high‐resolution optical correlation analysis, and joint optical‐InSAR slip inversion. Our preferred model, validated by the teleseismic multi‐peak moment rate release, includes unilateral eastward double‐onset supershear speeds and cascading rupture dynamically triggering two adjacent fault branches. We propose that pronounced along‐strike variation in fracture energy, complex fault geometries, and multi‐scale variable prestress drives this event's complex rupture dynamics. We illustrate how supershear transition has signatures in modeled and observed off‐fault deformation. Our study opens new avenues to combine observations and models to better understand complex earthquake dynamics, including local and potentially repeating supershear episodes across immature faults or under heterogeneous stress and strength conditions, which are potentially not unusual.